2010
DOI: 10.1007/s10552-010-9589-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in one-carbon metabolism pathway genes, urinary arsenic profile, and urothelial carcinoma

Abstract: Environmental factors played a more important role in UC carcinogenesis than MTHFR or MS gene polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…The public health implication of these findings is apparent when the BMI extremes in our pooled population are compared. The mean %uMMA in the upper and lower BMI deciles of our population were 13.8% and 9.4%, respectively, similar to the %uMMA difference reported between arsenic-associated urothelial carcinoma cases and controls (12.5% vs. 8.1%, respectively) (Chung et al , 2010). This suggests that the magnitude of the effect of BMI on arsenic methylation efficiency could be relevant to disease risk.…”
Section: Discussionsupporting
confidence: 87%
“…The public health implication of these findings is apparent when the BMI extremes in our pooled population are compared. The mean %uMMA in the upper and lower BMI deciles of our population were 13.8% and 9.4%, respectively, similar to the %uMMA difference reported between arsenic-associated urothelial carcinoma cases and controls (12.5% vs. 8.1%, respectively) (Chung et al , 2010). This suggests that the magnitude of the effect of BMI on arsenic methylation efficiency could be relevant to disease risk.…”
Section: Discussionsupporting
confidence: 87%
“…By contrast, Moore et al (19) reported conflicting results, suggesting a lower risk of bladder cancer was observed in individuals carrying either the Ala/Val or Val/Val genotype compared to those carrying the Ala/Ala genotype. The remaining 6 studies reported that there were no statistically significant associations between the Ala222Val polymorphism and bladder cancer risk (67,18,2021,26). For the variant genotypes of Glu429Ala polymorphism, Rouissi et al (6) reported that it was associated with a higher risk of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in a number of genes, including GSTO1 and GSTO2 from glutathione-S-transferase (GST) family which use glutathione as a reducing agent to catalyze pentavalent arsenicals to trivalent forms, GSTP1, GSTZ1, GSTM1, and GSTT1 of GSTs family which involved in the xenobiotic metabolism and play a role in the cellular response mechanism against oxidative stress induced by arsenic, arsenic 3-methyltransferase (AS3MT) which use S-adenosyl-methionine as a methyl donor to produce MMA and DMA, and methylene-tetrahydrofolate reductase (MTHFR) of one-carbon metabolism pathway, have been reported to be associated with the variation in arsenic methylation capacity [33-35] and susceptibility to arsenic-related skin lesions [36-38] and bladder cancer [39-42]. Since the role of gene polymorphisms in arsenic-related hypertension was rarely discussed which still need further research, we could not completely exclude the possible relationship between polymorphisms of these genes and susceptibility to the arsenic-related hypertension.…”
Section: Discussionmentioning
confidence: 99%